High‐resolution sub‐ice‐shelf seafloor records of twentieth century ungrounding and retreat of Pine Island Glacier, West Antarctica - Davies, D.; Bingham, R. G.; Graham, A. G. C.; Spagnolo, M.; Dutrieux, P.; Vaughan, D. G.; Jenkins, Adrian; Nitsche, F. O. (Journal of Geophysical Research: Earth Surface, 2017)
Pine Island Glacier Ice Shelf (PIGIS) has been thinning rapidly over recent decades, resulting in a progressive drawdown of the inland ice and an upstream migration of the grounding line. The resultant ice loss from Pine Island Glacier (PIG) and its neighboring ice streams presently contributes an estimated ∼10% to global sea level rise, motivating efforts to constrain better the rate of future ice retreat. One route toward gaining a better understanding of the processes required to underpin physically based projections is provided by examining assemblages of landforms and sediment exposed over recent decades by the ongoing ungrounding of PIG. Here we present high-resolution bathymetry and sub-bottom-profiler data acquired by autonomous underwater vehicle (AUV) surveys beneath PIGIS in 2009 and 2014, respectively. We identify landforms and sediments associated with grounded ice flow, proglacial and subglacial sediment transport, overprinting of lightly grounded ice-shelf keels, and stepwise grounding line retreat. The location of a submarine ridge (Jenkins Ridge) coincides with a transition from exposed crystalline bedrock to abundant sediment cover potentially linked to a thick sedimentary basin extending upstream of the modern grounding line. The capability of acquiring high-resolution data from AUV platforms enables observations of landforms and understanding of processes on a scale that is not possible in standard offshore geophysical surveys.